Strategi Komunikasi Pemasaran TATV Untuk Meningkatkan Jumlah Pengiklan - Christian, Mikael Kevin Hodie; Vanel, Zon (Universitas Prof. Dr. Moestopo (Beragama), 2023)
The television industry places itself in business competition to obtain commercial benefits for the company’s sustainability. The reduced number of television viewers has an impact on declining advertising revenue. To meet sales targets, companies must carry out various appropriate strategies to attract advertisers to buy the company’s products, namely through advertising. TATV has implemented various strategies but has not been able to increase significantly. This study aims to find out and describe how the marketing communication strategy is carried out by TATV to increase the number of advertisers. This research uses descriptive qualitative research with the case study method. Data collection techniques used are interviews, observation, and documentation. The results of this study indicate that the five marketing mixes, such as advertising, sales promotion, public relations, personal selling, and direct marketing, ara important to increase TATV sales. Of the 5 most frequently used marketing activities, personal selling is face to face selling or face to face with clients and online via WhatsApp and email. This is because it makes it easier for clients to be able to provide immediate feedback and frequent dealing or buying occurs.